Poloxamer®s anchored with TAT enhance blood-brain barrier penetration of carbamazepine for the treatment of epilepsy: an in vivo study - Farnaz Sotoudegan; Mohsen Amini; Mohammad Sharifzadeh; Nasrin Samadi; Farzaneh Sotoudegan (SpringerOpen, 2024)
Abstract Carbamazepine is a pharmacological medication commonly prescribed to treat epilepsy. Dose adjustments, poor bioavailability, and prolonged side effects present significant challenges associated with its use. Poloxamer micelles have demonstrated exceptional properties as nanocarriers for drug delivery. This research aimed to develop Poloxamer nanomicelles containing carbamazepine and assess their potential to cross the blood-brain barrier. Poloxamer 407 and P-85 micelles, anchored with TAT as a ligand and containing carbamazepine, were prepared. The morphology, entrapment efficiency, drug release, stability, and toxicity of nanomicelles were examined, along with animal studies conducted to evaluate their anticonvulsant effects. The distribution of carbamazepine-Poloxamer in the brain and plasma was assessed. The results indicated the successful formation of spherical nanomicelles with an average size of less than 100 nm, and carbamazepine was effectively incorporated into the micelles. Formulations composed of mixtures of Poloxamer exhibited a high encapsulation efficiency of approximately 92.1% and remained stable for three months. A sustained release of carbamazepine was observed for up to 72 h. The anticonvulsant effect of carbamazepine-loaded nanomicelles in mice was found to be significantly greater than that of those treated with carbamazepine solution, with the effect increasing by approximately tenfold. Compared to free carbamazepine, the carbamazepine-loaded nanomicelles exhibited a 5.5-fold increase in the brain targeting index, with no toxicity observed in mice treated with these nanomicelles. These findings suggest that Poloxamer micelles represent a promising nanoscale, controlled-release delivery system that is free from toxicity and can enhance the penetration of carbamazepine into the brain while improving its anticonvulsant activity. Graphical Abstract